Lessons learned from designing and evaluating an educational brain fitness program. Issue 2 (12th June 2017) - Nicholson, Roscoe; O'Brien, Catherine
Abstract : Purpose: The purpose of this paper is to provide aging services professional insights into older adult responses to brain fitness programs that may not appear on quantitative program evaluations. Design/methodology/approach: Qualitative data obtained via observations, instructor interviews and feedback, open-ended responses on course evaluations and participant focus groups. Findings: Participants come to brain fitness programs with a variety of expectations and preferences about program content. Some are looking for educational content, some wanted to learn memory strategies, and others are looking for drilling or brain games. Participants responded very positively to descriptions of brain fitness research and scientific details. However, presenting such content posed a challenge to non-expert instructors, and efforts should be made to reduce this burden. Instructors can play a valuable role in goal setting, but instructors and participants felt that small rewards for meeting goals were unnecessary. Both instructors and participants felt that peer-to-peer interaction is a particularly valuable component of such courses. Overburdening participants should also be avoided. Organizations offering the program were also found to be adapting the course to better fit the organization's capacities and the desires of participants. Research limitations/implications: The participant population is largely Caucasian, well-educated and middle to high socioeconomic status. Practical implications: Due to the characteristics of the participant population, it is not known which, if any, of the findings apply to a less well-educated, lower income populations, or populations from other racial/ethnic groups. Originality/value: These insights can assist senior living professionals in successfully creating, adopting or adapting brain fitness programs in order to best meet the needs of the populations that they serve.